2022
DOI: 10.1007/s10508-022-02311-w
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sexual Practices, Sexually Transmitted Infections and Other Genital Infections in Women Who Have Sex with Women Only (WSWO), Women Who Have Sex with Men Only (WSMO) and Women Who Have Sex with Men and Women (WSMW): Findings from a Sexual Health Clinic in Melbourne, Australia, 2011–2019

Abstract: Despite rises in sexually transmitted infection (STI) notifications among Australian women in the last decade, limited STI surveillance data exist specifically for women who have sex with women. This study aimed to compare differences in sexual practices and positivity for STIs and other genital infections among women who have sex with men only (WSMO), women who have sex with women only (WSWO), and women who have sex with men and women (WSMW), and whether these changed over time. In this retrospective repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Other studies have indicated BV to be more common among people of younger age and/or those who are black; 1,2 , 24-26 however, many other factors have also been associated with increased prevalence or risk of BV and its recurrence, including low socioeconomic status, alcohol and cigarette use, having multiple sexual partners, sexual orientation, obesity, vaginal care practices, and vaginal microbiome composition. 1,2 , 7-12 , 24-29 Given the age distribution of our study population was relatively consistent with that found in other Medicaid populations (2013-2017) in the published scientific literature, 30 but the proportion of black patients was higher, our data suggest that black patients with Medicaid coverage may be more affected by BV than other race/ethnicity groups. Medicaid programs cover >16 million women of reproductive age across the United States whose income is <200% of the federal poverty level with a high representation of racially and ethnically diverse women.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Other studies have indicated BV to be more common among people of younger age and/or those who are black; 1,2 , 24-26 however, many other factors have also been associated with increased prevalence or risk of BV and its recurrence, including low socioeconomic status, alcohol and cigarette use, having multiple sexual partners, sexual orientation, obesity, vaginal care practices, and vaginal microbiome composition. 1,2 , 7-12 , 24-29 Given the age distribution of our study population was relatively consistent with that found in other Medicaid populations (2013-2017) in the published scientific literature, 30 but the proportion of black patients was higher, our data suggest that black patients with Medicaid coverage may be more affected by BV than other race/ethnicity groups. Medicaid programs cover >16 million women of reproductive age across the United States whose income is <200% of the federal poverty level with a high representation of racially and ethnically diverse women.…”
Section: Discussionsupporting
confidence: 85%
“…[5][6][7] Other factors, such as baseline vaginal microbiome composition, biofilm accumulation, antimicrobial resistance, number of sexual partners, and sexual orientation, can also influence BV recurrence and its frequency. [7][8][9][10][11][12] There is very little information in published scientific literature of optimal treatment strategies for recurrent BV, except that there are few therapeutic options and a lack of progress in any methods of prevention. 7 The widespread occurrence of incident BV, high frequency of recurrence, and current treatment and prevention limitations all signify an unmet need for improving women's reproductive health care in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…MSW were defined as sexually active men who had never had sex with another man. Women were not stratified based on sexual practices due to the small number of women who have sex with women attending the MSHC ( 24 ). We calculated the straight-line distance between the individual’s residential postcode and the MSHC, to determine the distance from home to the MSHC.…”
Section: Methodsmentioning
confidence: 99%
“…1 A sharp increase in syphilis cases among heterosexual men and women, especially those of child-bearing age, Aboriginal and Torres Strait Islander peoples and women pregnant at the time of diagnosis, has caused considerable concern. 2 , 3 , 4 , 5 In particular, the increasing rate of syphilis in women of reproductive age has been identified as a public health priority due to its association with congenital syphilis, which is complicated by congenital defects, prematurity, low birth weight and stillbirth. 1 , 6 , 7 In Victoria, the proportion of syphilis cases that are women increased from 8.8% in 2016 to 12.8% in 2020.…”
Section: Introductionmentioning
confidence: 99%